A rare mechanism of aortic regurgitation in a young patient. Issue 12 (29th October 2017) - Guner, Ahmet; Gunduz, Sabahattin; Onal, Cagatay; Akgun, Taylan; Bayam, Emrah; Candan, Ozkan; Ozkan, Mehmet
Abstract : A 19‐year‐old male patient was admitted to our institute with dyspnea. His medical history had no rheumatic fever or infective endocarditis. Physical examination revealed a diastolic murmur over the aortic area, rales of bilateral lungs. Bedside transthoracic echocardiography (TTE) revealed a severe aortic regurgitation (AR) without aortic valve stenosis and a moderately dilated left ventricle accompanied by an ejection fraction of 55%. The aortic valve could not be clearly demonstrated as either bicuspid or tricuspid. Congenital AR typically occurs in conjunction with an additional cardiac abnormality or aortic valve stenosis. Furthermore, bicuspid aortic valves are observed in the majority of patients. The aortic valve is created from the truncus ridge of the truncus arteriosus while the embryological development.